Division of cortical cells is regulated by auxin in Arabidopsis roots - Kim, Huijin; Jang, Jinwoo; Seomun, Subhin; Yoon, Youngdae; Jang, Geupil (Frontiers in Plant Science, 2022)
The root cortex transports water and nutrients absorbed by the root epidermis into the vasculature and stores substances such as starch, resins, and essential oils. The cortical cells are also deeply involved in determining epidermal cell fate. In Arabidopsis thaliana roots, the cortex is composed of a single cell layer generated by a single round of periclinal division of the cortex/endodermis initials. To further explore cortex development, we traced the development of the cortex by counting cortical cells. Unlike vascular cells, whose number increased during development of root apical meristem (RAM), the number of cortical cells did not change, indicating that cortical cells do not divide during RAM development. However, auxin induced cortical cell division, and this finding was confirmed by treatment with the auxin transport inhibitor N-1-naphthylphthalamic acid (NPA) and examining transgenic plants harboring CO2::ΔARF5, in which cortical expression of truncated AUXIN RESPONSE FACTOR5 (ΔARF5) induces auxin responses. NPA-induced cortical auxin accumulation and CO2::ΔARF5¬-mediated cortical auxin response induced anticlinal and periclinal cell divisions, thus increasing the number of cortical cells. These findings reveal a tight link between auxin and cortical cell division, suggesting that auxin is a key player determining root cortical cell division.